Case report: Nighttime media restriction for pediatric insomnia - Arai, Yusuke; Sasayama, Daimei; Suzuki, Kazuhiro; Watanabe, Jun; Kuraishi, Yuta; Koido, Mika; Washizuka, Shinsuke (Frontiers in Sleep, 2024)
This report describes the case of a 13-year-old boy with chronic insomnia and increased daytime sleepiness linked to excessive nocturnal media use. Implementing a restriction on digital device usage after 9 pm led to a significant improvement in the sleep duration with no adverse event. Throughout the 16-week treatment period, the total sleep time of the patient normalized, and the daytime sleepiness problem was resolved. This is an indication that the treatment was effective. This case emphasizes the potential of nighttime screentime restriction in treating pediatric chronic insomnia and highlights the importance of addressing screen time in sleep disorder management.